2011
DOI: 10.1055/s-0031-1296850
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activities of Thiadiazine Derivatives against Leishmania amazonensis

Abstract: Ten thiadiazine derivatives were tested in vitro for antiparasitic effects against both extracellular promastigotes and intracellular amastigotes of Leishmania amazonensis. The results showed that the evaluated compounds exhibited a strong antiproliferative activity on all developmental stages of the parasite. The minimal inhibitory concentration and the 50 % effective concentration values against the promastigote were 2.1-5.1 microg/ml and 0.6-1.8 microg/ml, respectively. The tested compounds caused an irreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…These results confirmed that the THTT represent a group of compounds with significant in vitro activity against L. amazonensis and suggested that some of them could be considered for further study as new therapeuthic alternatives [32,33]. …”
Section: Biological Activity Of Thtt Derivativessupporting
confidence: 59%
See 2 more Smart Citations
“…These results confirmed that the THTT represent a group of compounds with significant in vitro activity against L. amazonensis and suggested that some of them could be considered for further study as new therapeuthic alternatives [32,33]. …”
Section: Biological Activity Of Thtt Derivativessupporting
confidence: 59%
“…8 ) were tested in vitro for antiparasitic effects against both extracellular promastigotes and intracellular amastigotes of Leishmania amazonensis [32,33] . The compounds were found to be active against the amastigote form of the parasite, inhibiting parasite growing, from 10 to 89%, at a concentration of 100 µg/mL.…”
Section: Biological Activity Of Thtt Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The antiparasitic properties of some 5-carboxyalkyl-3-furfuryl-1,3,5-thiadiazinane-2-thione against both extracellular promastigotes and intracellular amastigotes of Leishmania amazonensis have also been reported. 18,19 The results showed that the evaluated compounds exhibited a strong antiproliferative activity on all developmental stages of the parasite. Following our ongoing project to develop new antiparasitic agents using the THTT ring as the central core, we have also reported the synthesis and biological activity of bis(1,3,5-thiadiazinane-2-thiones) derivatives where the two thiadiazinane rings are linked by an alkyl chain 20 or a linear polyamine moiety.…”
Section: Introductionmentioning
confidence: 96%
“…21 Taking to account the interaction mechanism suggested for this heterocycle, the incorporation of two THTT moiety in the same structure must increase the activity of these derivatives as antiparasitic agents. 22 We have previously demonstrated the feasibility of the synthesis of thiadiazinane-2-thiones in solution [14][15][16][18][19][20][21] by reaction of the appropriate amine with carbon disulfide and potassium hydroxide, to give the dithiocarbamate potassium salt, which is not isolated, followed by cyclocondensation with formaldehyde and the selected amino acids or pseudopeptides able to provide the nitrogen atom at the N-5 position of the thiadiazinane ring. Based on experimental evidence and DFT studies, a probable cyclization route to 1,3,5-thiadiazinane-2-thiones in aqueous medium was proposed.…”
Section: Introductionmentioning
confidence: 99%